Measuring Teachers’ Readiness to Adopt Organizational Loyalty Philosophy - Joanna Rosak-Szyrocka; Ali Abdulhassan Abbas (Communications of International Proceedings, 2020)
Primary school education is one of the basic issues in society. The effectiveness of schools and the extent of its impact on society are measured on the basis of teachers’ loyalty, love, attachment to school and their desire to continue their work in the school. This gets reflected in the increased level of creativity in displaying scientific material and its delivery to students clearly. The current study is aimed at identifying the degree of organizational loyalty among teachers in Aleamid School for boys and girls and the most important obstacles that lead to weak organizational loyalty.
Keywords: Organizational Loyalty; Emotional Dimension; Constant Loyalty; Standard Loyalty.